2015
DOI: 10.21101/cejph.a4017
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Self-Esteem in Early Adolescence

Abstract: SUMMARYAim: Depression prevalence has increased in the last few decades, affecting younger age groups. The aim of this research was to determine the range of depression and low self-esteem in elementary school children in the city of Split. Testing was carried out at school and the sample comprised 1,549 children (714 boys and 832 girls, aged 13).Methods: Two psychological instruments were used: the Coopersmith Self-Esteem Inventory (SEI) and the Children and Adolescent Depression Scale (SDD).Results: The aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Con frecuencia, la autoestima y la confianza en sí mismo surgen como elementos importantes en el desarrollo social. Algunos estudios sugieren que participar en actividades musicales puede mejorar los niveles de confianza y autoestima, lo que a su vez tiene repercusiones positivas para el bienestar mental (Zarobe & Bungay, 2017), mientras que otros sugieren que desempeña un papel importante en la prevención de problemas psicoemocionales entre niños y adolescentes (Tripkovic et al, 2015). La cooperación necesaria para crear música de forma colectiva puede mejorar el nivel de autoestima y la diversión en mayor medida que las actitudes y actividades musicales competitivas (Lowe, 2018).…”
Section: El Impacto De La Práctica Musical Grupal En El Desarrollo So...unclassified
See 1 more Smart Citation
“…Con frecuencia, la autoestima y la confianza en sí mismo surgen como elementos importantes en el desarrollo social. Algunos estudios sugieren que participar en actividades musicales puede mejorar los niveles de confianza y autoestima, lo que a su vez tiene repercusiones positivas para el bienestar mental (Zarobe & Bungay, 2017), mientras que otros sugieren que desempeña un papel importante en la prevención de problemas psicoemocionales entre niños y adolescentes (Tripkovic et al, 2015). La cooperación necesaria para crear música de forma colectiva puede mejorar el nivel de autoestima y la diversión en mayor medida que las actitudes y actividades musicales competitivas (Lowe, 2018).…”
Section: El Impacto De La Práctica Musical Grupal En El Desarrollo So...unclassified
“…Self-esteem and self-confidence frequently emerge as important elements in social development. Some studies suggest that engaging with musical activities can raise self-esteem and self-confidence, which has positive repercussions for mental well-being (Zarobe & Bungay, 2017), while others show it plays an important role in preventing psycho-emotional problems among children and teenagers (Tripkovic et al, 2015). The cooperation involved in making music together can enhance self-esteem and enjoyment to a greater extent than competitive musical activities and attitudes do (Lowe, 2018).…”
mentioning
confidence: 99%
“…The difference in the degree of association between social capital and depression might be accounted for by the expression of depressive symptoms which varies according to the developmental stage [83][84][85]. Since early adolescents exhibit depressive mood and despair as the symptoms of major depressive disorder [85,86], the score of "school trust and social cohesion" could be more strongly associated with the DSRS-C score which mainly contains items of depressive mood in junior high students (Fig 1). Conversely, in elementary students (Fig 3A ), the score of "school trust and social cohesion" could be more strongly associated with the PedsQL score that includes the physical functioning subscale related to physical symptoms of depression because prepubescent children tend to display physical symptoms of major depression [83][84][85].…”
Section: Inter-educational Stage Differences (Among Elementary and Ju...mentioning
confidence: 99%
“…Compared to healthy individuals, patients with MDD have a lower self‐attitude at an explicit level (Auerbach et al, 2015; Ji et al, 2017; Kiang et al, 2017; Y. Li et al, 2017). Some studies have found that low self‐esteem is directly related to depression (Tripkovic et al, 2015; Yoo et al, 2015) and indirectly related to SI (Lin, 2015a). Other studies have revealed the mediating role of self‐esteem in the relationship between negative/stressful events and depression/suicide (An et al, 2016; J. Y. Kim & Lee, 2015; Lin, 2015b; Yusufov et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al, 2017). Some studies have found that low self-esteem is directly related to depression (Tripkovic et al, 2015;Yoo et al, 2015) and indirectly related to SI (Lin, 2015a). Other studies have revealed the mediating role of self-esteem in the relationship between negative/stressful events and depression/suicide (An et al, 2016; J. Y.…”
Section: Introductionmentioning
confidence: 99%